HOW GENDER AFFECT RELATIONSHIPS BETWEEN VARIABLES IN INFORMATION SYSTEMS USAGE AND USER SATISFACTION MODEL - Mardiana, Siti; Garlinia Yudawisastra, Helin; Nurbaeti Amin, Neneng; Tri Utami, Alia; Parihah Nurasiah, Sofa (Penerbit Lafadz Jaya, 2026)
This paper aims to explore the role of gender as moderating variables for the relationships between variables in the modified information system success model. This research is needed to uncover whether the gender gap exists in information system implementation. The result of the study This digitization in organization which focus on its impact for defining the usage of information system and user satisfaction. A quantitative study using PLS-SEM had been employed to reveal whether gender has influence on the relationships between variables. A data collection was conducted using questionnaire which was distributed in a private university. There are 146 data from respondents that can be used for data analysis. Using both PLS algorithm and bootstrapping procedure in SmartPLS®, several findings can be excerpt from the analysis. First, gender affects the relationship between information quality and actual use. Second, gender does not have impact on the relationship between system quality and actual use, perceived benefit and actual use, service quality and actual use, actual use and user satisfaction. As general conclusion, gender does not impact most factors of the information system usage and satisfaction model. This result is promising in term of gender role in digitation process in organization since gender gap mostly does not exist. Further analysis and implications are discussed in the article.